Assessment of sustainable urban mobility indicators for the city of São Mateus, ES - Oliveira, Vinicius Almeida de; Feroni, Rita de Cassia (Brazilian Journal of Production Engineering, 2022)
The mobility system of a city has a direct impact on the population’s quality of life, implying the way in which citizens enjoy the right to come and go, as well as the possibility of accessing basic services. In this context, the objective of the present study consists of evaluating the sustainable urban mobility index for the municipality of São Mateus, ES, from 2013 to 2020, in the social, economic and environmental dimensions. For this, a bibliographic survey was carried out in order to identify the set of indicators that would best suit the study based on the availability of data. As main results resulting from the research, an average for the Global Sustainable Urban Mobility Index of 0,5146 was identified, positive result within the evaluated scale (between 0 and 1), highlighting the good performance obtained for the social dimension (0,6678). As for the indicators, a poor performance was observed regarding public investments, family budget spent in the transport sector and the use of alternative fuels and clean energy. A good performance was identified for the indicators of accidents involving pedestrians and cyclists, and urban facilities (schools). Therefore, it was possible to conclude that the methodology adopted showed potential for identifying positive and negative points in the local transport system, and can be used to assist the public authorities in defining strategies to improve sustainable urban mobility in the municipality.